1998
DOI: 10.1074/jbc.273.33.20867
|View full text |Cite
|
Sign up to set email alerts
|

Structural Determinants Present in the C-terminal Binding Protein Binding Site of Adenovirus Early Region 1A Proteins

Abstract: The C-terminal binding protein (CtBP) has previously been shown to bind to a highly conserved six-amino acid motif very close to the C terminus of adenovirus early region 1A (Ad E1A) proteins. We have developed an enzyme-linked immunosorbent assay that has facilitated the screening of synthetic peptides identical or similar to the binding site on Ad E1A for their ability to bind CtBP and thus inhibit its interaction with Ad12 E1A. It has been shown that amino acids both C-terminal and N-terminal to the origina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
50
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 53 publications
4
50
0
Order By: Relevance
“…A recent study of the CtBPbinding site in E1A indicated that the initial proline residue in PXDLS was extremely important for the efficient binding and mutation to alanine dramatically reduced the affinity between CtBP and a peptide (19). Consistent with this observation, various cross-species comparisons of well characterized CtBPbinding sites showed that the initial proline is almost invariably conserved (15,18).…”
Section: Ebna3a Binds To Gst-ctbp Through Two Cryptic "Pldlslike" Seqsupporting
confidence: 58%
See 1 more Smart Citation
“…A recent study of the CtBPbinding site in E1A indicated that the initial proline residue in PXDLS was extremely important for the efficient binding and mutation to alanine dramatically reduced the affinity between CtBP and a peptide (19). Consistent with this observation, various cross-species comparisons of well characterized CtBPbinding sites showed that the initial proline is almost invariably conserved (15,18).…”
Section: Ebna3a Binds To Gst-ctbp Through Two Cryptic "Pldlslike" Seqsupporting
confidence: 58%
“…All these various factors that regulate transcription and bind to CtBP contain a conserved Pro-X-Asp-Leu-Ser ("PXDLS") CtBPinteraction domain that is necessary and probably sufficient for the interaction. The conserved proline and leucine residues are generally considered essential for efficient binding (15,18,19). A second mammalian CtBP was recently described and the two family members, which are referred to as CtBP1 and CtBP2, are largely homologous although they may have distinct tissue distributions (20).…”
mentioning
confidence: 99%
“…Most interactions involving CtBP occur through the binding motif, PXDLS. Recent studies, however, have suggested that the binding site in E1A for CtBP extends over a slightly larger sequence than originally suggested (48). In many instances, this motif is followed at the carboxyl-terminal end by a Lys residue, but the function of this Lys has never before been addressed.…”
Section: Discussionmentioning
confidence: 87%
“…It is likely, therefore, that the fraction of E1A that is acetylated at Lys-239 is highly deficient in its ability to bind CtBP. To determine the effects of the E1A mutations and acetylation more quantitatively, we used an ELISA (48). Briefly, this method involved mixing a GST-fusion protein containing the carboxyl-terminal 67 amino acids of E1A (GST-E1ACter) with immobilized full-length CtBP in the presence of varying concentrations of wild-type and mutated E1A peptides.…”
Section: E1amentioning
confidence: 99%
“…There are a number of reasons for this, over expression of E1A in eukaryote cells leads to apoptosis (White, 1998), the majority of E1A expressed in E. coli is insoluble or it may have only limited structure until it is complexed with partner proteins (Bayley and Mymryk, 1994). Using peptide mimicry and NMR spectroscopy we have resolved structures for the N-terminal portion of CR3, the TBP binding site (Molloy et al, 1999), this was found to form an a helix whilst the CtBP binding site (including the PXDLS motif, Shaeper et al, 1995) formed a series of b turns (Molloy et al, 1998). Bioinformatic predictions suggest that E1A also has secondary structure at the Nterminus over the region where a number of cellular proteins bind (Molloy, personal communication).…”
mentioning
confidence: 99%